Major Shift On Screen:Historical Significance Of New Wave Movies In Malayalam - Akshara B S (CV. Radja Publika, 2026)
The new wave Malayalam films played an important role in Indian film history and it introduced realistic social criticisicm and artistic experimentation in Malayalam movies. Directors like Adoor Gopalakrishnan G Aravindan ,K G George etc express to Kerala society in a more realistic manner and through their films they portrayed caste,class, gender and other social evils in more realistic manner. It is very relevant today to analyse how films can be used as historical sources. Films like 'Swayamvaram','Elippathayam','Uttarayanam','Kumari' captured Kerala's Complex socio political and cultural complexities.It also examine how Malayalam new wave movement influenced films of other Indian languages .Change in the representation of women in Malayalam movies,change in narrative structure,response of society about the social transformation in Kerala,and how new wave malayalam movies were accepted globally and screened in film festivals were analysed.aNew wave movies were entirely different from commercial movies.It challenged mainstream narratives and introduced realistic and complex themes .To analyse Kerala's shift from traditional society to modern,new wave malayalam movies served as a historical document.This paper examines how new wave malayalam movies reshaped India's film narration,and how much a new wave malayalam movie can be used as a powerful historical source.